Resource-friendly carbon fiber composites: combining production waste with virgin feedstock. (2nd October 2017) - Kratz, James; Low, Yi Shane; Fox, Ben
Abstract: Reclaimed carbon fiber materials were studied in this paper with the aim of improving virgin fiber feedstock usage. Both processing and mechanical properties were investigated. The compaction response showed lower fiber volume fractions in reclaimed fiber materials than the virgin continuous reinforcement from which it was reclaimed. In addition, localized high-strain regions were observed during consolidation of the dry fiber and mechanical loading of cured laminates. These vulnerable failure points were mitigated by incorporating virgin continuous fiber feedstock into the laminate. A knock-down in mechanical properties was observed, however classical laminated plate theory identified a planar stiffness drop of 3.5 GPa for every 10% increase in reclaimed carbon fiber content in a continuous fiber laminate. Increased feedstock usage by combining both virgin and reclaimed carbon fibers was shown to be viable option to implement more resource efficient, but heavier, composite structures. Graphical abstract: